The Impact of Hyaluronic Acid on Tendon Physiology and Its Clinical Application in Tendinopathies - Francesco Oliva (MDPI AG, 2021)
The physical–chemical, structural, hydrodynamic, and biological properties of hyaluronic acid within tendons are still poorly investigated. Medical history and clinical applications of hyaluronic acid for tendinopathies are still debated. In general, the properties of hyaluronic acid depend on several factors including molecular weight. Several preclinical and clinical experiences show a good efficacy and safety profile of hyaluronic acid, despite the absence of consensus in the literature regarding the classification according to molecular weight. In in vitro and preclinical studies, hyaluronic acid has shown physical–chemical properties, such as biocompatibility, mucoadhesivity, hygroscopicity, and viscoelasticity, useful to contribute to tendon healing. Additionally, in clinical studies, hyaluronic acid has been used with promising results in different tendinopathies. In this narrative review, findings encourage the clinical application of HA in tendinopathies such as rotator cuff, epicondylitis, Achilles, and patellar tendinopathy.